Determination of the Radiation Hazard Indices and Excess Lifetime Cancer Risk in Iraqi Bentonite - Ahmed, Rasha S; Mohammed, Raghad S; Kharbat, Ahlam Rashid (Al-Nahrain Journal of Science, 2018)
The activity concentrations for 232Th, 238U, 40K, and 137Cs were measured in bentonite samples using high purity germanium detector. These samples were collected from the main distribution markets in Baghdad, the capital of Iraq. The mean activity concentrations for 232Th, 238U, 40K and 137Cs were found to be 6.10, 5.89, 162 and 1.8 Bq/kg respectively. The results of specific activities were less than the recommended global values by (UNSCEAR, 2000). The radiation hazard indices in therapeutic bentonite have been also measured. The total air absorbed dose rate, the annual effective dose, the radium equivalent activity, the external hazard index and the excess lifetime cancer risk have a mean value of 13.2 nGy/h, 0.0000162 Sv, 27 Bq/kg, 0.073, and 0.000053 respectively. Low radiation hazard indices were recorded. These low levels indicated that the mud is safe, and suitable to be used in therapy, also the dealer with this mud are not exposed to any radiation hazards.